Isolation of Human Osteoblast Cells Capable for Mineralization and Synthetizing Bone-Related Proteins In Vitro from Adult Bone - Daria Kostina; Arseniy Lobov; Polina Klausen; Vitaly Karelkin; Rashid Tikhilov; Svetlana Bozhkova; Andrey Sereda; Nadezhda Ryumina; Natella Enukashvily; Anna Malashicheva (Cells, 2022)
The culture of osteoblasts (OB) of human origin is a useful experimental model in studying bone biology, osteogenic differentiation, functions of bone proteins, oncological processes in bone tissue, testing drugs against bone desires, and many other fields. The purpose of the present study is to share a workflow that has established the conditions to efficiently isolate and grow OB cells obtained from surgically removed bones from human donors. The protocol described here also shows how to determine cell phenotype. Here we provide characteristics of cells isolated by this protocol that might help researchers to decide if such OB are suitable for the purposes of their study. Osteoblasts isolated from collagenase-treated explants of adult bones are able to proliferate and keep their phenotype in culture. OB cells have high synthetic properties. They express osteomarkers, such as RUNX2, osteocalcin, BMP2, and osteopontin both in control conditions and in an osteogenic medium that could be estimated by qPCR and immunocytochemical staining and by Western blotting. Induction of osteogenic differentiation does not dramatically influence the synthetic properties of OB cells, while the cells gain the ability to extracellular mineralization only in an osteogenic medium.